Study of some Rheological Properties and Determine the Optimal Use of Mixtures of Wheat Flour and some Types of Legumes Flour - Alhommada, Wisal Ali; Ibrahim, Theeb delly; Gergi, Raymond Spiro; El- Masry, Mohamed (Journal of agricultural, environmental and veterinary sciences, 2020)
Study of some Rheological Properties and Determine the Optimal Use of Mixtures of Wheat Flour and some Types of Legumes FlourThis research aims to study some rheological properties of mixtures of wheat flour, lentil flour and bean flour separately (10%, 20% and 30%), using different parameters of the mixolab  according to ICC.No.173 method; the required grain samples were obtained from the 2018 season. Grinding using a laboratory mill, at the rate of three replicates per sample, and all analyzes were conducted in the laboratory of grain technology, Faculty of Agricultural Engineering, Al- Furat University.The results of protein estimation showed that there were significant differences when adding different lentil and bean flour levels. Also, there was a significant difference in the average percentage of water absorbed with different substitution rates. and its found significant difference in the average of the time of dough formation with the longer time with Lentil flour 20%, and replacement rate of bean flour 30%.The results also showed that the average falling number was marked by the increase in the replacement rate 20% lentil flour and 20% bean flour (426 and 437 seconds, respectively), which corresponds to the starch gelatin speed.The mean torque of the protein impairment phase was highest 0.57 Nm and 0.51 Nm for replacement rates of 30% for both lentil and bean flour.Decrease in phase C5 torque with increasing substitution rate of bean flour up to 30% which is positively reflected on delayed appearance of staling and prolonged shelf life of baked products for storage.
Keywords: wheat flour; rheological properties; staling; mixolab; lentil flour; bean flour